2019
DOI: 10.3389/fpls.2019.00033
|View full text |Cite
|
Sign up to set email alerts
|

Spring Is Coming: Genetic Analyses of the Bud Break Date Locus Reveal Candidate Genes From the Cold Perception Pathway to Dormancy Release in Apple (Malus × domestica Borkh.)

Abstract: Chilling requirement (CR) for bud dormancy completion determines the time of bud break in apple (Malus × domestica Borkh.). The molecular control of bud dormancy is highly heritable, suggesting a strong genetic control of the trait. An available Infinium II SNP platform for genotyping containing 8,788 single nucleotide polymorphic markers was employed, and linkage maps were constructed in a F1 cross from the low CR M13/91 and the moderate CR cv. Fred Hough. These maps were used to identify quantitative trait l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 83 publications
(140 reference statements)
1
25
0
Order By: Relevance
“…Next, we investigated the function of apple MADS TFs during dormancy, as previous genetic and molecular evidence highlighted their roles during the dormancy cycle [4,5,16,25,46,47]. To gain insights whether the observed physical interactions between apple MADS TFs have biological relevance during dormancy, the transcript levels of their encoding genes were quantified during an annual time course (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated the function of apple MADS TFs during dormancy, as previous genetic and molecular evidence highlighted their roles during the dormancy cycle [4,5,16,25,46,47]. To gain insights whether the observed physical interactions between apple MADS TFs have biological relevance during dormancy, the transcript levels of their encoding genes were quantified during an annual time course (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…By examining the transcript level of PmDAM6 in the mapping population, they proposed that DAM6 may act as a repressor for bud break in a dose-dependent manner in P. mume (Kitamura et al, 2018). A similar QTL study on apple identified a major QTL related to timing of bud break on LG9 that contained orthologs of ICE1, FLOWERING LOCUS C (FLC), and PACLOBUTRAZOL RESISTANCE 1 (PRE1) that are possibly involved in mediating bud break in apple trees (Miotto et al, 2019). With the development of next-generation sequencing, genome-wide association mapping has become an alternative for genetic linkage mapping (Jackson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Even the mechanism of chemicals known to help overcome dormancy and promote budbreak (i.e., hydrogen cyanamide) is yet to be described (35). It is possible that this is due to the fact that most studies compare species and genotypes with "low chill" and "high chill" requirement based on time to budbreak [e.g., (36)(37)(38)]. The results presented here suggest that those chill requirements are mostly a result of a genotype's response to forcing (r = -0.78) and not different stages of dormancy.…”
Section: Implications Of a Conserved Dormancy Progressionmentioning
confidence: 99%
“…However, there are still questions about which temperatures promote chilling and how much chilling they provide (26,27), leading to multiple methods for estimation of chill accumulation based on temperature (28)(29)(30)(31)(32). This is in part due to the fact that a mechanism for dormancy has yet to be resolved, despite a growing list of dormancy related genes and chemicals that promote dormancy transitions (33)(34)(35)(36)(37)(38). Recent work has shown that rates of cold hardiness loss (deacclimation) increase with chilling accumulation, which can be used to study dormancy progression (24).…”
Section: Introductionmentioning
confidence: 99%